‘Turning up and tuning in’. Factors associated with parental non‐attendance and non‐adherence in intervention for young children with speech, language communication needs - Williams, Penny; Slonims, Vicky; Weinman, John (International journal of language & communication disorders, 2024)
Background When parents bring their child to appointments and then adhere to agreed speech and language therapy (SLT) recommendations, there is the potential to increase the intensity of the intervention, support generalization and improve outcomes. In SLT, however, little is known about factors that may promote attendance or adherence. Studies in other clinical areas such in medicine, psychology and physiotherapy have identified risk factors for non‐attendance or non‐adherence that are multifactorial and variable dependent on, for example, population and intervention. Aims To identify rates of non‐attendance and non‐adherence, and to identify parent or child factors associated with parent involvement in intervention for children under 5 years of age receiving SLT. Methods Parents completed questionnaires at two time points assessing the domains of parents’ beliefs (problem perceptions, self‐efficacy), personal circumstances (socio‐demographics, family functioning), treatment experience and child factors. Predictors of parent attendance and adherence were identified through multiple regression analyses. Non‐attendance rates were identified via local health records and non‐adherence ascertained using a specific parent‐reported measure within the treatment experience domain. Results Participants (N = 199) were predominantly mothers, and were ethnically and socio‐economically diverse, speaking a wide range of languages. Their children presented with a range of speech, language communication needs (SLCN). The rate of non‐attendance was 25% and the main predictors of non‐attendance were maternal age, education level and two factors within the parent beliefs domain. This model explained 40% of the variance in attendance. The rate of non‐adherence in this cohort was 26% with parental rating of the importance of a recommendation and self‐efficacy beliefs predicting adherence; this explained 56% of the variance in adherence to SLT recommendations at home. Conclusions & Implications Our research has provided preliminary evidence of the influence of parents’ beliefs, personal circumstances and treatment experiences on their involvement in their child's therapy. Speech and language therapists should consider factors impacting attendance and adherence to treatment and explore parental perceptions of their child's SLCN before embarking on an intervention, a foundation for collaborative practice. A possible limitation of this study is that the levels of attrition in our sample led to generally high measured rates of participation, which should be considered in future studies. Future research should explore adherence in treatments with varying doses, with different types of SLCN or interventions and in different settings. WHAT THIS PAPER ADDS What is already known on the subject It is acknowledged that parent involvement in their child's therapy, such as attending and adhering to recommendations, is important but little is known about the rates of involvement and what factors may be associated with attendance and adherence in SLT. Qualitative research has explored parental involvement suggesting that beliefs about an intervention may be pertinent. Extensive research in other clinical areas suggest multiple and varied factors are influential and further exploration of particular populations and interventions is necessary. What this paper adds to the existing knowledge This study identified rates of parental non‐attendance and non‐adherence in a cohort of predominantly mothers of children under the age of 5 years. It is the first study to measure parent adherence in SLT and identify factors that are associated parental adherence to SLT recommendations. It adds to the small body of SLT specific research in understanding risk factors for non‐attendance. What are the potential or actual clinical implications of this work? This study highlights the need for a speech and language therapist to consider and explore parents' perspectives of their child's SLCN as a part of achieving collaboration with a parent in order to achieve the best outcomes. It provides a foundation for further systematic research into parent involvement with the ultimate aim of enhancing outcomes for children with SLCN.